Oral health status and selected salivary physicochemical characteristics among a group of patients with acute lymphocytic leukemia undergoing chemotherapy (longitudinal study) (Mustansiria Dental Journal, 2019)
Background: Acute lymphoblastic leukemia is fast growing cancer of the whiteblood cell. Chemotherapy which has been used to treat malignant conditions has anegative impact on oral health condition among cancer patients. Thisobservational study was conducted to determine the level of selected salivaryphysicochemical characteristics including flow rate and total antioxidant) inaddition to evaluation of oral health status (dental plaque and gingival healthcondition) among a group of patients with acute lymphoblastic leukemia.Materials and methods: The present study included thirty patients with acutelymphoblastic leukemia aged (14-17) years old. Those patients attended MedicalCity in Baghdad and were admitted to the Hematological Center at TeachingBaghdad Hospital. All patients fullfitted certain inclusion criteria. Salivary samplecollection and oral examination were carried at three visits: the first visit wascarried out before receiving chemotherapy (at the day of admission)(baselinedata), while the second visit was carried out at the day 15 (after startingchemotherapy), and the third visit was done at the day 30 (after startingchemotherapy). Stimulated salivary samples were collected and salivary flow ratewas determined. Dental plaque was assessed according to criteria of plaque indexby Sillness and Lӧe (1964) and gingival health condition was assessed accordingto the criteria of Modified Gingival Index for Lobene et al (1986). Salivarysamples then were chemically analyzed for the detection of salivary totalantioxidant.Results: In this study, salivary flow rate decreased with time (visits) (1.44±0.14,1.27±0.16, 1.02±0.53) with statistically highly significant differences (p